The Role of Translation in the Development of Scientific Knowledge in the Premodern Islamic World - Khalid Hussain Mir; Md. Rafique Anjum (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper examines the profound impact of the translation movement on the development of scientific knowledge in the premodern Islamic world, focusing on the Abbasid Caliphate (8th to 10th centuries). The establishment of the